Variations in gut microbiota associated with changes in life-history traits of Daphnia galeata induced by fish kairomones - Choi, Tae-June; An, Hyung-Eun; Mun, Min-Ho; Han, Seung-Min; Kim, Chang-Bae (Frontiers in Ecology and Evolution, 2024)
The gut microbiota plays a crucial role in host physiology and the disruption of host-microbiota relationships caused by environmental stressors can impact host growth and survival. In this study, we used Daphnia galeata as a model organism to investigate the interactive effects of fish kairomones on the life-history traits and gut microbiota alterations of D. galeata, as well as the relationship between life-history traits and gut microbiota composition. The presence of fish kairomones enhanced fecundity, decreased growth, and altered gut microbiota, with significant changes in alpha diversity but not in beta diversity in the genotype KB5 of D. galeata. Statistical analysis revealed that the relative abundance of the Pseudomonadaceae family significantly increased upon exposure to fish kairomone, while the relative abundance of the Comamonadaceae family significantly decreased. The decreased growth in genotype KB5 may be associated with a significant increase in Pseudomonas, a member of the family Pseudomonadaceae, which is generally deficient in essential fatty acids, potentially negatively impacting growth. Meanwhile, it is speculated that the significant decrease in Limnohabitans belonging to the Comamonadaceae family is associated with the reduction of body size and increased fecundity of KB5 when exposed to fish kairomones. These data suggest that variations in host life-history traits related to reproduction and growth are potentially associated with the relative abundance or presence of these microbial genera. Our research findings provide valuable insights into understanding the impact of biotic stress on the interaction between hosts and microbiota.